(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The practice of literary theory became prominent in the nineteenth century. Literary theory is an organized study and analysis of literature with application of some principles and methods. Since time immemorial nature has been the integral part of literature, many prominent poets and writers of every age have glorified nature and its other aspects in their works. However, the issues like degradation of nature under the name of development and modernity, ecological imbalance became the subject of serious concern for the literary artists very recently. This new way of judging literature and manifestation of nature in literature gave birth to novel approach in the field of literary theory, which is knows as ecocriticism. The term ecocriticism or ecocritic is made of two words, eco and critic. These two words have been derived from Greek words oikos and kritis meaning house judge. Here, we can take house for surroundings or environment in which we live and the word judge for a person who examines the quality of environment, factors responsible for its degradation and suggests some remedies to rectify the damage done. In this paper the scholar aims to analyse Raksha Bharadia‟s write-up on nature titled as Alchemy of Nature with a ecocritical point of view to analyse a role of nature as a motivating force for human beings and explaining the bond between nature and a man.